Hacia una enseñanza de lenguas extranjeras basada en el desarrollo de la interacción comunicativa - Martínez Agudo, Juan de Dios (Didáctica. Lengua y Literatura, 2003)
This article emphasizes the value of communicative interaction in the foreign language classroom which exerts a significant influence on the quality of language learning. Through interaction, linguistic-communicative development is enhanced. Therefore, it is fundamental to promote the quality of communicative interaction that has to be exploited